Penetapan Kadar Triprolidina Hidroklorida dan Pseudoefedrina Hidroklorida Dalam Tablet Anti Influenza Secara Spektrofotometri Derivatif - Hayun, Hayun; Harianto, Harianto; Yenti, Yenti (Majalah Ilmu Kefarmasian, 2006)
The determination of triprolidine hydrochloride and pseudoephedrine hydrochloride in anti influenza tablet has been performed using derivative spectrophotometry method. Triprolidine hydrochloride and pseudoephedrine hydrochloride were determined by measuring the first derivative ratio amplitudes, at 227,6 nm (zero crossing for pseudoephedrine hydrochloride) and at 230,0 nm (zero crossing for triprolidine hydrochloride) respectively. The linear calibration graphs were obtained for 5-50 ppm of triprolidine hydrochloride and for 100-800 ppm of pseudoephedrine hydrochloride. The results showed that the method is rapid, simple and can be applied successfully to assay simultaneously of two components in tablet preparation.